1983
DOI: 10.1111/j.1365-2621.1983.tb05106.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Models for Moisture Dependence of Ascorbic Acid and β‐Carotene Degradation in Dehydrated Sweet Potato

Abstract: Mathematical models which describe the effect of water activity on the rate of loss of ascorbic acid and p-carotene in a dehydrated sweet potato system were developed under isothermal storage conditions at 40°C. The p-carotene model was verified in several batches of sweet potato. It was found that, although the absolute magnitudes of the rates showed differences between batches, the model form remains appropriate for describing the effects of moisture. There fore, the models seem to be general, but model para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…The situation was also similar to other vegetable juice fermentation [25]. Boiling at 100 • C for 15 min substantially reduced β-carotene content from 180 mg/kg in fresh tuber to 140 mg/kg in fully-boiled tuber [26]. This amount remained more or less same after fermentation (Table 1).…”
Section: Enzymatic Extraction Of Sp Lacto-juicesupporting
confidence: 83%
“…The situation was also similar to other vegetable juice fermentation [25]. Boiling at 100 • C for 15 min substantially reduced β-carotene content from 180 mg/kg in fresh tuber to 140 mg/kg in fully-boiled tuber [26]. This amount remained more or less same after fermentation (Table 1).…”
Section: Enzymatic Extraction Of Sp Lacto-juicesupporting
confidence: 83%
“…Previous research on freeze-dried sweet potato cubes also showed higher levels of β-carotene degradation at lower water activities [71].…”
Section: Effect Of Food Compositionmentioning
confidence: 90%
“…It is therefore essential to optimise Orange Flesh Sweet potato (OFSP) processing conditions in order to achieve products with high nutritional quality (Jackobsen, 2011). The reduction effect of boiling on β-carotene content of sweet potatoes was reported as early as 1980s (Haralampu & Karel, 1983). In some pioneering studies regarding the effect of fermentation on β-carotene, reported that β-carotene remained more or less the same after fermentation, i.e.…”
Section: Effects Of Lactic Acid Fermentation On the β-Carotene Contenmentioning
confidence: 99%